Design, analysis and fabrication of manual food slicer machine / Muhammad Fareed Johari - Johari, Muhammad Fareed (2022)
Food preparation is an important part in food industry. Not only that, but many people in every house also tend to have a safety problem and says that it is time consuming if we used only a knife to cut and it is hard to handle for some certain people which not really good in kitchen. Therefore, the purpose of this project is to design, analyse and fabricate the manual food slicer machine. Most of the food processor is imported and of course it is costly. For this project, the manual food slicer machine will be able to apply for fresh food such as vegetables and fruits. The development of this machine begins by identifying problems that occurs to people who have problem in kitchens. Then, studies on the food processor that available in market which are directly related are next in line. Then, the machine is design based on the concept adapted from the problems faced. Next, careful material selection process begins to make sure the material used is safe for user and easy to be washed. Next process is which comparison of different type of slicer machines are done and followed by data collected from the survey that have done. After that, in Final Year Project 2, the process of fabricating is done for 14 weeks